O difícil diálogo entre escola e mídia - Zanchetta, Juvenal [UNESP] (FapUNIFESP (SciELO), 2017)
Since the 1930s, when the Estado Novo organized the secondary and higher school in Brazil, and also when it outlined how the mass Media would come to address the issue of education, formal school and Media have always gone different ways, although the educational purpose is a determining factor to the two institutions. In this paper, we investigate the reasons to this characteristic, especially with regard to secondary school. The main reason for that distancing is the isolation of secondary school in relation to the Media, because of the regulatory legislation and the pedagogical tendencies for the school action. The references for the analysis were the federal curricular legislation and guidelines for secondary school (1930s-2016s), the textbooks for Portuguese (1970s-2016s), and the journal Revista Brasileira de Estudos Pedagógicos (1940s-1960s). Among the more general findings are the secondary strategy of approaching school and the Media through the option for vehicles and projects of the state (a determining tendency since the 1930s); and the increasing exposure of Media texts in the daily life of pedagogical actions from the 1970s, but with a predominance of activities aimed at attending the regular curriculum, far from the evaluation of the media context.
The difficult dialogue between secondary school and the Media in Brazil
Keywords: Formal education; Media; Secondary school